1990
DOI: 10.1130/spe255-p201
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the provincial signature of Early Permian faunas of the eastern Klamath terrane

Abstract: The abundant and well-studied Early Permian faunas of the eastern Klamath terrane, which contain a high percentage of endemic species and genera, constitute part of a biotic province (the McCloud province) that is distinct from the better known central Cordilleran and Tethyan provinces. The McCloud province evidently fringed an island arc that was located within the tropical climatic zone of the Paleopacific Ocean during the Early Permian. The development of an endemic biota in this province required considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…This scenario is supported by biogeographic analyses of Permian fauna in the eastern Klamath terrane, which Stevens et al (1990) suggested formed at least 5000 km outboard of the Cordilleran margin. A fourth model calls on changes in subduction geometry to explain the interplay between arc magmatism and accretion of ocean-floor assemblages ( Fig.…”
Section: Geologic and Tectonic Frameworkmentioning
confidence: 92%
“…This scenario is supported by biogeographic analyses of Permian fauna in the eastern Klamath terrane, which Stevens et al (1990) suggested formed at least 5000 km outboard of the Cordilleran margin. A fourth model calls on changes in subduction geometry to explain the interplay between arc magmatism and accretion of ocean-floor assemblages ( Fig.…”
Section: Geologic and Tectonic Frameworkmentioning
confidence: 92%
“…Tethyan faunas in some of the limestone blocks were pantropic forms that migrated into island chains of the proto-Pacifi c Ocean west of Mesozoic North America (Miller and Wright, 1987;Newton, 1988). Tectonic transport estimated from paleofaunal interpretations as thousands of kilometers of longitude was required to bring the Tethyan limestones to the Cordilleran continental margin (Stevens et al, 1990(Stevens et al, , 1991Belasky and Stevens, 2006).…”
Section: Continental Truncationmentioning
confidence: 98%
“…Locally severe dislocation of Western Hayfork volcanic rocks to the condition of broken formation can then be understood as a structural overprint imposed during accretion of an intraoceanic arc assemblage to the edge of the growing continent. Limestone cobbles in the Western Hayfork belt contain McCloud fauna , native to tropical island settings, which from paleofaunal analysis were initially at least 1000 km and possibly >5000 km from the continental margin of Laurentia (Stevens et al, 1990).…”
Section: Western Hayfork-rattlesnake Creek Beltsmentioning
confidence: 99%
“…[49] The presence of Permian macrofossils of McCloud belt affinity at several localities on the Slide Mountain and Yukon-Tanana terranes (see summary by , together with paleomagnetic results suggesting ∼2000 km of northward displacement of PennsylvanianPermian rocks of the Slide Mountain assemblage in the Sylvester allochthon [Richards et al, 1993], has led some workers to speculate that the Slide Mountain ocean must have been several thousand kilometers wide [e.g., Stevens et al, 1990;Nelson et al, , 2009. Our dating results help constrain the possible size and tectonic evolution of the Slide Mountain ocean basin.…”
Section: Implications For the Size And Evolution Of The Slide Mountaimentioning
confidence: 99%